Evaluation of Performance and Response of Broiler Chickens Fed Diets with Graded Levels of Pawpaw (Carica papaya) Leaf Meal (Sahel Journal of Life Sciences FUDMA, 2025)
This study determined the growth performance and carcass characteristics of broiler chickens fed diets containing graded pawpaw (Carica papaya) leaf meal levels. A total of one hundred and fifty (150) day-old chicks were brooded for two weeks before being randomly allotted to five dietary treatments T1, T2, T3, T4, and T5 containing varying inclusion levels of Carica papaya leaf meal at 0%, 1.5%, 3% 4.5% and 6% respectively. Data collected include nutrient intake, nutrient digestibility, and growth performance measurements. At the end of the experiment, two birds were randomly selected from each of the three replicates of the dietary treatments and were slaughtered for carcass evaluation. The study found no significant differences (p>0.05) in live, bled, de-feathered, eviscerated, or dressed weights, organ weights, and primal cuts percentages across broiler chicken treatments, except for the gizzard weight which varied significantly (p